Effect of Employee Perception of Sex Diversity and Employee Perception of Retaining Sex Diversity on Work Efforts Mediated By Interactional Justice, Distributive Justice, and Procedural Justice in Public Sector - Yohanes Rico Ananda Putra; Muhammad Irfan Syaebani (Syntax Corporation, 2023)
Digital transformation has become one of the government programs. In an organization full of diversity, leaders need to carry out good governance. Proper diversity management is needed for organizations with diverse employees. Diversity management can be felt by employees from two perspectives, namely how employees see the existing diversity and how employees see the organization's efforts to maintain diversity. Apart from being applied to managing organizations, diversity management is directly proportional to organizational justice. This research aims to determine the effect of perceptions of sex diversity and perceptions of retaining sex diversity on employee work efforts in the public sector mediated by interactional justice, distributive justice, and procedural justice in organizations. Research data was collected using a questionnaire and obtained 148 respondents. The collected data was analyzed using the Partial Least Square (PLS-SEM) based Structural Equation Modeling method with the SmartPLS application. The results showed that there was a positive effect on perceptions of employee diversity and perceptions of retaining employee diversity on work effort mediated by procedural justice. However, the results showed that other variables had a different effect. This research contributes to providing an overview regarding how to improve the work efforts of employees in the public sector, especially those with a high level of diversity.